Low energy hadron production data and current status of CERN measurements - Barr, G; Engel, R (2006)
Data on low-energy hadron production in collisions of nucleons, pions and kaons with light nuclei are needed for many astrophysical and accelerator applications. Modern simulations have reached a level of accuracy that the lack of detailed understanding of hadron production processes has become one of the most important limitations to further improvements. After giving some examples of hadro-production processes in astrophysics and neutrino experiments we briefly review existing fixed-target data on light nuclei. Preliminary results and prospects of current CERN measurements (HARP, NA49) are discussed.